Efficient cutaneous wound healing using bixin‐loaded PCL nanofibers in diabetic mice. Issue 7 (13th June 2016) - Pinzón‐García, Ana Delia; Cassini‐Vieira, Puebla; Ribeiro, Cyntia Cabral; de Matos Jensen, Carlos Eduardo; Barcelos, Luciola Silva; Cortes, Maria Esperanza; Sinisterra, Ruben Dario
Abstract: The present work demonstrated an efficient cutaneous wound healing using Bixin‐loaded polycaprolactone (PCL) nanofibers as a controlled delivery system. The influence of Bixin (Bix) content on PCL nanofiber, Bix‐PCL1(2.5% w/w bix) and Bix‐PCL2 (12.5% w/w bix) formation was investigated using electrical conductivity, attenuated total reflectance infrared spectroscopy, X‐ray diffraction, thermal analysis, and scanning electronic microscopy. The results showed that a greater bixin concentration resulted in higher polymeric solution electrical conductivity. Moreover, higher polymeric solution electrical conductivity provides lower nanofibers in terms of average diameter than pure PCL nanofibers. In vitro release was largely governed by a diffusion‐controlled mechanism. The initial Bixin release domain showed a burst release over the first 10 hours where approximately 30% and 40% of Bixin was released from Bix‐PCL1 and Bix‐PCL2 nanofibers, respectively. The second kinetic domain was comprised of a continuous and slow Bixin release that led to almost 100% of the Bixin being released within 14 days. The results on excisional wound model in induced diabetic mice indicated that the low concentration of Bixin released from loaded Bix‐PCL nanofibers maintain the biological activity of Bixin and is efficient in accelerating the wound healing as well as in reducing the scar tissue area compared with pure PCL nanofibers. Therefore, soft material Bixin‐loaded PCL nanofibers are a promising candidate for use in wound dressing. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1938–1949, 2017.